Article processing charge may be a barrier to publishing - Jain, Vijay Kumar (J Clin Orthop Trauma, 2020)
Recently most of the journals charge a fee known as article processing charge (APC) for publication of an article. These charges can vary from journal to journal. This publication fee is often paid by the author, the author’s institution, or their research funder organization. Though low- and middle-income countries are usually exempted from APC, India does not come under the category of waiver by most of the journals that ask for the APC. Most of the Indian institutes do not pay for publication and research thus individual researcher suffers huge financial burden due to APC. Hence, less affluent institutions, scholars, and students are unable to publish their work due to these barriers. These articles highlight the challenges faced by authors and solutions for publishers and journals to avoid APCs.